PENDEKATAN INTERDISIPLINER DALAM TAFSIR AL-QUR’AN : INTEGRASI ANTARA ILMU TAFSIR DAN ILMU SOSIAL - Sufyan Muttaqin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is to examine the interdisciplinary approach in the interpretation of the Qur'an by integrating the science of interpretation and social sciences. The purpose of the study is to understand the integration between the science of interpretation and social sciences. The research method used is library research, where data is collected from various relevant literature sources. The results of the study indicate that the interdisciplinary approach allows a more comprehensive understanding of the text of the Qur'an, taking into account the social, cultural, and historical contexts. The integration between the science of interpretation and social sciences provides a new perspective in interpreting the verses of the Qur'an, so that it can answer the challenges and needs of contemporary society. The conclusion of this study is that the interdisciplinary approach in the interpretation of the Qur'an is very important to develop a more holistic and applicable understanding of Islamic teachings.